Venom Concentrations and Clotting Factor Levels in a Prospective Cohort of Russell's Viper Bites with Coagulopathy. - Geoffrey K Isbister; Kalana Maduwage; Fiona E Scorgie; Seyed Shahmy; Fahim Mohamed; Chandana Abeysinghe; Harendra Karunathilake; Margaret A O'Leary; Christeine A Gnanathasan; Lisa F Lincz (Public Library of Science (PLoS), 2015)
BACKGROUND:Russell's viper envenoming is a major problem in South Asia and causes venom induced consumption coagulopathy. This study aimed to investigate the kinetics and dynamics of venom and clotting function in Russell's viper envenoming. METHODOLOGY/PRINCIPAL FINDINGS:In a prospective cohort of 146 patients with Russell's viper envenoming, we measured venom concentrations, international normalised ratio [INR], prothrombin time (PT), activated partial thromboplastin time (aPTT), coagulation factors I, II, V, VII, VIII, IX and X, and von Willebrand factor antigen. The median age was 39 y (16-82 y) and 111 were male. The median peak INR was 6.8 (interquartile range [IQR]: 3.7 to >13), associated with low fibrinogen [median,<0.01 g/L; IQR: <0.01-0.9 g/L), low factor V levels [median,<5%; IQR: <5-4%], low factor VIII levels [median,40%; IQR: 12-79%] and low factor X levels [median, 48%; IQR: 29-67%]. There were smaller reductions in factors II, IX and VII over time. All factors recovered over 48 h post-antivenom. The median INR remained >3 at 6 h post-antivenom but had reduced to <2, by 24 h. The aPTT had also returned to close to normal (<50 sec) at 24 h. Factor VII, VIII and IX levels were unusually high pre-antivenom, median peak concentrations of 393%, 307% and 468% respectively. Pre-antivenom venom concentrations and the INR (r = 0.20, p = 0.02) and aPTT (r = 0.19, p = 0.03) were correlated (non-parametric Spearman analysis). CONCLUSIONS:Russell's viper coagulopathy results in prolonged aPTT, INR, low fibrinogen, factors V, VIII and X which recover over 48 h. Severity of clotting abnormalities was associated with venom concentrations.